Business strategy : plan, execute, win - Stroh, Patrick J., 1969- (Hoboken, NJ : Wiley, 2014)
"In today's fast-moving and competitive business environment, strong leadership, insightful strategy, and effective innovation are critical links to staying ahead of your competition. Getting your business house in order can often be complicated, but does it really have to be? How do you take MBA 101 lessons, great models, and exceptional concepts and put them into play in the real world? Business Strategy: Plan, Execute, Win! strives to answers these questions in an educational and entertaining format. Working as a Fortune 20 practitioner with C-level executives, author Patrick Stroh has a keen understanding of the role played by current day strategists. With 5 chapters following the format of "All I Ever Needed to Learn About Business Strategy I Learned..." At the Movies, On the Farm, On Shark Tank, On Hell's Kitchen, and From the Bible, readers will gain valuable strategic insight regardless of industry, business maturity, or current business turbulence and how to apply these insights based on the factors impacting their own business. Each chapter ends with a One Chapter Conclusion, Two Gold Nuggets the reader is to write down and Three Additional Resources/Tools for more information, offering a practical roadmap to simplifying your success"--
Chapter 7: Everything I Needed to Learn about Business Strategy I Learned . . . from Shark TankTypical Questions the Sharks Ask All Presenters; Round 2: Shark Personalities; Summary; Part III: Tools, Resources, and Conclusions; Chapter 8: The Strategy Toolbox and Other References; 13 Lucky Models and Methods; Personal Top 12 Most Valuable Business Books of All Time; One Final Tool; Chapter 9: Winning Checklist: How to Succeed in Business Strategy; Winning Conclusions and Summary; A Closing Song; About the Author; Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Strategic planning; Leadership; BUSINESS & ECONOMICS / Management; Management; Leadership; Strategic planning; Electronic books; Electronic books